anlatırmısınız lütffen
![Anlatırmısınız Lütffen class=](https://tr-static.eodev.com/files/d3f/b7c3d6511fb2fff0c05813234083ca00.jpg)
Cevap:
Adım adım açıklama:
➠ Cevap ektedir.
☘Anlamadığın bir yer olursa sorabilirsin.
ⓘⓨⓘ ⓓⓔⓡⓢⓛⓔⓡ ;)
⚘ce
Cevap:
A şıkkı
Adım adım açıklama:
l.yol
f(x+1)= 2x+3
f^-1(2x+3)= x+1
2x+3= 3 , x= 0
f^-1(2.0+3)= 0+1
f^-1(3)= 1 olur.
ll.yol
f(x)'i bulalım
y= x+1= x= y-1 bunu f(x+1)'de yerine yazarsak
f(x+1-1)= 2.(x-1)+3
f(x)= 2x+1 olur. tersi y= 2x+1, y=( x-1)/2 yani
f^-1(x)= (x-1)/2 olur.
f^-1(3)= (3-1)/2= 1 olur.